Ground-coupled heat pump systems: a pumping analysis - Mays, Cristin Jean (Kansas State University, 2012)
Ground-coupled heat pump (GCHP) systems use the ground as a heat source or sink that absorbs heat from or rejects heat to the soil, respectively; this is referred to as the geothermal heat exchanger. Apart from the geothermal heat exchanger, there are two other main system components that make up a GCHP system: heat pumps and circulation pumps. This report studies four GCHP pumping systems and makes comparisons between the four using life-cycle cost analyses for six building models. The goal for this analysis was to discover commonalities between the models in order to provide designers insight into which pumping system is the most cost effective. The analysis was performed by first creating energy models to obtain system and zone load information, as well as system part-load data and geothermal heat exchanger performance. From the zone load information, heat pump selections were then performed to indicate the worst case piping path that is required for pump head calculations. Piping layouts were created to establish pipe lengths for the pump head calculations as well. Other piping components such as valves and fittings and the air separator pressure drops were also calculated. Once the pump head calculations were complete for each system, pump schedules were created. From there initial unit and installation costs were determined for each pump, as well as their replacement costs. The part-load data from the energy models were then used to obtain annual pump energy consumption and pump utility cost. Finally, assumptions were made to establish regular and preventative maintenance requirements for each pumping system. Initial and replacement unit costs, annual utility cost and regular and preventative maintenance costs were the components used in the life-cycle cost analysis. Each of these components was converted to 30-year projected costs and added to create a total life-cycle cost for each pumping system. Comparisons were then made and the results showed that a primary pumping system with VFD control and 100% redundancy was the most cost effective system. However, there are other considerations such as controllability, flexibility and availability that might persuade designers to choose one of the other alternate solutions.
Keywords: Ground-coupled; Heat pump; Pumping system; HVAC; Ground-source; Distributive; Architectural engineering (0462)